Autoimmune hepatitis after COVID-19 vaccine – more than a coincidence. Issue 125 (December 2021) - Garrido, Isabel; Lopes, Susana; Simões, Manuel Sobrinho; Liberal, Rodrigo; Lopes, Joanne; Carneiro, Fátima; Macedo, Guilherme
Abstract: The COVID-19 pandemic is still raging across the world and vaccination is expected to lead us out of this pandemic. Although the efficacy of the vaccines is beyond doubt, safety still remains a concern. We report a case of a 65-year-old woman who experienced acute severe autoimmune hepatitis two weeks after receiving the first dose of Moderna-COVID-19 vaccine. Serum immunoglobulin G was elevated and antinuclear antibody was positive (1:100, speckled pattern). Liver histology showed a marked expansion of the portal tracts, severe interface hepatitis and multiple confluent foci of lobular necrosis. She started treatment with prednisolone, with a favorable clinical and analytical evolution. Some recent reports have been suggested that COVID-19 vaccination can lead to the development of autoimmune diseases. It is speculated that the vaccine can disturb self-tolerance and trigger autoimmune responses through cross-reactivity with host cells. Therefore, healthcare providers must remain vigilant during mass COVID-19 vaccination. Highlights: A 65-year-old woman was diagnosed with autoimmune hepatitis after receiving the first dose of SARS-CoV-2 vaccine. Liver histology showed inflammatory portal infiltrate with interface hepatitis, centrilobular inflammation and necrosis. The patient showed improvement in liver function tests and normalization of IgG levels under treatment with corticosteroids. Molecular mimicry is a potential mechanism for COVID-19 vaccine-induced autoimmunity.